Segmentation algorithms of biomedical images: development and quantitative evaluation - Berezsky, O.; Batko, Yu.; Melnyk, G.; Verbovyy, S.; Pitsun, O. (Штучний інтелект, 2016)
The article presents the comparative analysis of the biomedical image segmentation methods. The work discusses segmentation methods on the basis of previous labeling and spatial moments. The experimental results show that the developed methods have higher accuracy by signal-noise ratio compared to the nowadays known. Moreover the authors have developed the quantitative evaluation of the segmentation algorithms based on the metrical approach. У статті представлений порівняльний аналіз методів сегментації біомедичних зображень. У роботі досліджуються методи сегментації на основі попередньої розмітки та просторових моментів. Експериментальні результати показують, що розроблені методи мають більш високу точність за співвідношенням сигнал-шум у порівнянні з відомими. Крім того, автори розробили алгоритм кількісної оцінки алгоритмів сегментації на основі метричного підходу. The proposed research has been developed within the state budget project "Hybrid Intelligent Information Technology Diagnosing of Precancerous Breast Cancer Based on Image Analysis" (state registration number 1016U002500).